Left-sided renal colic as a symptom of advanced stomach cancer – a case report - Godlewski, Janusz; Kuciel-Lisieska, Grażyna; Licznerska, Grażyna; Tenderenda, Michał (Contemporary Oncology/Współczesna Onkologia, 2012)
The typical symptoms of advanced cancer of the stomach are well known in clinical practice. The presented case concerns a patient with symptoms of left-sided renal colic, caused by a malignant tumour involving the ureter, which was diagnosed with a CT scan. The multifocal process, involving the stomach, two parts of the colon, the left ovary and the side of the pelvis, was confirmed only during surgery. The resection or partial resection of the above-mentioned organs involved by the malignant process and reconstruction of the alimentary tract as well as the ureter were performed at time of this operation. The patient’s recovery was without any complications. The histopathological findings support the diagnosis of this malignant process as disseminated stomach cancer. In the available literature only two cases of stomach cancer metastasis to the ureter have been described. In both cited examples resection of the ureter with nephrectomy was performed. The review of the literature supports the value of stomach palliative resection in prolonging life and improving quality of life.